Procedimento para condução do teste de envelhecimento acelerado em sementes de algodão - Goncalves Souza, Fabiany Lilyani [UNESP]; Tomaz, Camila de Aquino [UNESP]; Rosolem, Ciro Antonio [UNESP]; Martins, Cibele Chalita [UNESP]; Cavariani, Cláudio [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2009)
The evaluation of the effect of seed has been fundamental tool in the program of quality control, and the accelerated aging test, an important part of that process. Some authors report that the germination and vigor are associated with seed size and facing the lack of consensus for the use of this test methodology and the relationship of seed size on the physiological quality, this work aimed to adapt the existing methodology as the temperature and period of conditioning on the performance of two sizes of seed cotton. The seeds were classified into two meshes of sieves, and then subjected to tests of water content, germination and electrical conductivity. The experimental design was completely randomized, analyzed statistically in a factorial threefold. Seeds of different sizes, showed no difference in percentage of germination. Seeds subjected to 40 degrees C for 42h of conditioning showed better percentage of germination.

A avaliação do vigor de sementes tem sido ferramenta fundamental dentro do programa de controle de qualidade, sendo o teste de envelhecimento acelerado, parte importante desse processo. Alguns autores relatam que a germinação e o vigor, estão associados ao tamanho das sementes e diante da falta de consenso para o emprego da metodologia deste teste e da relação do tamanho das sementes na qualidade fisiológica, o presente trabalho teve por objetivo adequar a metodologia existente quanto à temperatura e período de condicionamento, sobre o desempenho de dois tamanhos de sementes de algodão. As sementes foram classificadas em duas malhas de peneiras, e em seguida, submetidas aos testes de teor de água, germinação e condutividade elétrica. O delineamento experimental utilizado foi o inteiramente casualizado, analisado estatisticamente em esquema fatorial triplo. Sementes de tamanhos diferentes, não apresentaram diferença de porcentagem de germinação. Sementes submetidas à 40ºC por 42h de condicionamento apresentaram melhor porcentagem de germinação.
Procedure for conduction of the test of accelerated aging in cotton seeds
Keywords: Gossypium hirsutum; test vigour; seed classification